Popularity of hypoxic training methods for endurance-based professional and amateur athletes - Alvarez-Herms, J.; Julia-Sanchez, S.; Hamlin, M. J.; Corbi, F.; Pages, T.; Viscor, G. (Physiology & Behavior, 2015)
Scientific debate continues into whether hypoxic training has any performance benefit for athletes, and although this type of training seems popular, to our knowledge little empirical evidence on its popularity with endurance-based athletes exists. To quantify the usage of hypoxic training in endurance-based athletes we asked 203 athletes (amateur = 108, professional = 95) to complete a 17-question survey during 2013-2014 season. Compared to amateurs, professional athletes were 4.5 times (3.0-6.8, odds ratio, 95% confidence limits) more likely to undertake hypoxic training. Live-high train-low was the most popular hypoxic training protocol for athletes (52% professional and 80% amateur) with live-high train-high also used (38% professional, 20% amateur). Compared to amateurs, professional athletes tended to use evidence-based hypoxic training methods, seek advice on hypoxic training from reliable sources and were generally more realistic about the potential performance gains as a result of hypoxic training. Almost one third (25-30%) of all athletes suffered illness during their hypoxic training. Compared to amateurs, professional athletes are more likely to undertake hypoxic training and tend to follow current scientific guidelines. Attenuation of the ill effects that occur during hypoxic training may be accomplished if athletes give more attention to monitoring stress and training levels.